PENGARUH KOMPETENSI PEDAGOGIK DAN KECERDASAN SPIRITUAL TERHADAP PRESTASI KERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN PAYUNG SEKAKI PEKANBARU - Nursyalina Nursyalina; Suarman Suarman; Muhammad Nasir (Universitas Riau, 2017)
The purpose of this research is to know the effect of pedagogical competence andspiritual intelligence on the achievement of the State elementary school teachers’ achievementKecamatan Payung Sekaki Pekanbaru. This research is based on the importance of work performanceespecially teachers in educational institutions. However, not all teachers have demonstrated maximumwork performance. This is allegedly associated with the level of pedagogic competence and spiritualingenuity possessed by the teacher. This study was conducted at State Elementary School inKecamatan Payung Sekaki Pekanbaru That is as many as 116 samples, this data is obtained byusing questionnaire and documentation and analyzed using multiple linear regression. Based on theresult of research, it is known that there is a significant influence between pedagogical competenceand spiritual intelligence towards the achievement of the elementary school teacher in KecamatanPayung Sekaki Pekanbaru, Both partially or simultaneously. This means that the high achievement ofteachers ‘work achievement is influenced by pedagogical competence and spiritual intelligence, thehigher the mastery of teachers’ pedagogic competence, the higher the teacher’s work performanceand so on. Therefore, in order to increase teacher work performance, teachers’ pedagogic competenceimprovement is needed, through training or workshops.